Complete distribution of the genus Laevilitorina (Littorinimorpha, Littorinidae) in the Southern Hemisphere: remarks and natural history - Rosenfeld, Sebastian; Maturana, Claudia S.; Spencer, Hamish G.; Convey, Peter; Saucede, Thomas; Brickle, Paul; Bahamonde, Francisco; Jossart, Quentin; Poulin, Elie; Gonzalez-Wevar, Claudio (My University, 2022)
Littorinid snails are present in most coastal areas globally, playing a significant role in the ecology of intertidal communities. Laevilitorina is a marine gastropod genus distributed exclusively in the Southern Hemisphere, with 21 species reported from South America, the sub-Antarctic islands, Antarctica, New Zealand, Australia and Tasmania. Here, an updated database of 21 species generated from a combination of sources is presented: 1) new field sampling data; 2) published records; 3) the Global Biodiversity Infor-mation Facility (GBIF) and The Atlas of Living Australia (ALA), to provide a comprehensive description of the known geographic distribution of the genus and detailed occurrences for each of the 21 species. The database includes 813 records (occurrences), 53 from field sampling, 174 from the literature, 128from GBIF, and 458 from ALA. West Antarctica had the highest species richness (8 species), followed by sub-Antarctic islands of New Zealand (4 species) and the south-east shelf of Australia (4 species). The provinces of Magellan, New Zealand South Island, and sub-Antarctic Islands of the Indian Ocean include two species each. This study specifically highlights reports of L. pygmaea and L. venusta, species that have been almost unrecorded since their description. Recent advances in molecular studies of L. caliginosa showed that this species does not correspond to a widely distributed taxon, but to multiple divergent line-ages distributed throughout the Southern Ocean. Ongoing molecular and taxonomic studies are necessary for a better understanding of the diversity and biogeography of this genus.
Keywords: antarctic endemism; laevilitorininae; sub-antarctic